2000
DOI: 10.1034/j.1399-0039.2000.560604.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I and class II allele distribution in the Peruvian population

Abstract: The distribution of HLA-A, -B, -C, -DRB1 and -DQB1 alleles in the Peruvian population was studied and compared with those of other populations in order to provide further information about their anthropological origin. Our data are consistent with the Mestizo character of this population. In terms of genetic distance Peruvians are closest to Bolivians, which is in agreement with the geographical location and the cultural and anthropological background of the two human groups. Several HLA-B alleles originally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
13
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 2 publications
11
13
0
2
Order By: Relevance
“…In addition, the low frequency of CCR5Δ32 allele observed in our population did not allow us to further investigate the possible influence on Chagas’disease outcome. On the other hand, the low distribution of the CCR5Δ32 allele in the Peruvian sample is consistent with its anthropological origin, which is a mestizo population with a strong Amerindian component (18). Similar to our findings various studies have confirmed the low prevalence of the Δ32 allele among Amerindian populations (15, 19, 20), and corroborate the hypothesis that the CCR5Δ32 allele has a European origin, and that its presence in South American populations is probably the result of immigration.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, the low frequency of CCR5Δ32 allele observed in our population did not allow us to further investigate the possible influence on Chagas’disease outcome. On the other hand, the low distribution of the CCR5Δ32 allele in the Peruvian sample is consistent with its anthropological origin, which is a mestizo population with a strong Amerindian component (18). Similar to our findings various studies have confirmed the low prevalence of the Δ32 allele among Amerindian populations (15, 19, 20), and corroborate the hypothesis that the CCR5Δ32 allele has a European origin, and that its presence in South American populations is probably the result of immigration.…”
Section: Discussionsupporting
confidence: 73%
“…As expected, the most polymorphic locus was DRB1 and DRB1 * 09 : 01 the most common among its allelic variants (25% individuals). These results are in line with the findings from earlier studies across different Amerindian populations and more than double the available data on HLA allele frequencies in the Peruvian population. However, without the ability of better defining the ethnic origin of the participants in the present study beyond the self‐assigned “mestizo” origin, our data do not offer new insights into indigenous population of Peru.…”
supporting
confidence: 92%
“…Los alelos más frecuentes fueron el A*02 (22,5 %) y el A*24 (20,2 %), lo cual coincide con los datos reportados en otros estudios en Colombia, en Latinoamérica y en la población hispana en general, los cuales evidencian que estos dos alelos aparecen con una frecuencia superior al 40 % (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionunclassified
“…En el locus B fue posible detectar 43 alelos, de los cuales el 40 % se presentó con frecuencias inferiores a 1 %. Solo el B*35 tuvo una frecuencia superior a 20 %, es decir, fue el más representativo, tal como se ha registrado para la población colombiana y latinoamericana en otros estudios (11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionunclassified